Aquinas on the four last things : everything you need to know about death, judgment, heaven, and hell - Vost, Kevin (Manchester Sophia Institute press, 2020)
"Summarizes and provides reflections on Thomas Aquinas's writings on the four last things: death, judgment, heaven, and hell"--
Includes bibliographical references.
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274.; Eschatology